1983
DOI: 10.1084/jem.157.3.987
|View full text |Cite
|
Sign up to set email alerts
|

Arsonate-specific murine T cell clones. I. Genetic control and antigen specificity

Abstract: Thymus-derived lymphocytes exert a number of regulatory and effector activities in the immune system. Evidence has accumulated in recent years that these activities are largely executed by distinct subsets of T cells that can be distinguished by particular cell surface antigens (1, 2). This has led to the concept of a complex network of T cell types, each endowed with its own specific function. Rigorous proof of this concept has been difficult to achieve with heterogeneous cell populations. Recently, it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Early work using heterogeneous hapten-reactive T cells showed that T cells, like antibodies, could discriminate between related haptens (1,2,(4)(5)(6). Studies with clones of helper and cytolytic T cells have confirmed this conclusion (7)(8)(9). The premise of our work was that by using hapten-reactive T cell clones and hapten analogues, the structural features of a hapten that were important for activation might be identified.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Early work using heterogeneous hapten-reactive T cells showed that T cells, like antibodies, could discriminate between related haptens (1,2,(4)(5)(6). Studies with clones of helper and cytolytic T cells have confirmed this conclusion (7)(8)(9). The premise of our work was that by using hapten-reactive T cell clones and hapten analogues, the structural features of a hapten that were important for activation might be identified.…”
Section: Discussionsupporting
confidence: 52%
“…The most selective T cells show at least the ability of antibodies to make fine discriminations between arsonate and its analogues. Certain immunization regimens may elicit primarily the selective antibodies (34,36) or the selective T cells (4,9), while others elicit both classes of response (this study).…”
Section: Discussionmentioning
confidence: 95%
“…Perhaps this lower affinity results in lower levels of the type of T cell help (e .g ., Th2) required for isotype switching to IgGI due to less efficient B cell antigen capture, resulting in lower levels of antigen presentation to Th cells. Alternatively, a significant fraction of the memory Th population may have been primed to Ars (42,43), or an epitope that consists of an Ars-modified peptide subfragment of KLH. If this were true, the Sulf-KLH boost may not cross-stimulate the Ars-KLH-induced memory Th population as efficiently as it does the Ars-KLH-induced memory B cell population, perhaps leading to lower levels of isotype switching.…”
Section: Discussionmentioning
confidence: 99%
“…Different functional types of T cells have been induced that are specifi c for ABA including helpers (5, 6, 62), suppressors (109,161), killers (154), and mediators of delayed hypersensitivity reactions (11, 169). Very recently, long-term cultures of T cells specifically reactive to ABA-T were established from the lymph node cells of A/] mice, which had been immunized with ABA-T, and the cells were cloned by limiting dilution (70). The MHC restriction of the antigen-induced proliferation response of the clones was assayed with accessory cells from appropriate recombinant strains of mice and monoclonal anti-Ia antibodies as blocking reagents.…”
Section: Studies With T-cell Clonesmentioning
confidence: 99%